HUBUNGAN FREKUENSI MAKAN JUNK FOOD DENGAN STATUS GIZI SISWA KELAS X SMA KARTINI BATAM - Susanti, Rini; Rusdani, Rusdani (Universitas Batam, 2020)
Adolescents are the group that most often visits fast food restaurants that sell a lot of junk food, even up to three times a week. Junk food has an unbalanced nutrient content. This study aims to determine the relationship between the frequency of eating junk food and the nutritional status of 10th grade students at SMA Kartini Batam.This research method uses a cross-sectional design carried out at Batam Kartini High School. The sampling technique uses Slovin formula with a sample of 52 students. Data collection using questionnaires and anthropometric measurements. Data analysis using Spearman rank correlation test.From 22 respondents with a percentage (42.3%) whose frequency of eating junk food is rare and 28 respondents with a percentage (53.8%) have normal nutritional status. Based on the correlation test it is known that there is a significant relationship between the frequency of eating junk food and nutritional status in students with p value 0,000. Based on the results of this study it can be concluded that there is a significant relationship between the frequency of eating junk food and nutritional status in 10th grade students at SMA Kartini Batam in 2018.